Thermodynamics Study of Interaction Between β-Lactoglobulin with Sodium Dodecyl Sulfate, Dodecyl Trimethyl Ammonium Bromide and their Mixtures - Khabaz, M.; Housaindokht, M.R.; Chamani, J. (Asian Journal of Chemistry, 2010)
The interactions of bovine β-lactoglobulin (β-LA) with anionic surfactant sodium dodecyl sulfate (SDS), cationic surfactant dodecyl triethyl ammonium bromide (DTAB) and the mixtures of cationic-anionic surfactants (SDS-DTAB) have been carefully investigated by fluorescence, UV and circular dichroism (CD) techniques to elucidate the effect of these ligands on its structure. At pH 7.0 β-LA is negatively charged, therefore the absorbance of β-LA increased with the addition of SDS and the interaction of SDS with β-LA was the most distribution hydrophobic and a slight red shift of maximum peak position (from 275-278 nm) was observed, while DTAB had the different behaviour. The DTAB with β-LA had blue shift and the first electrostatic and the second hydro-phobic interactions. Therefore UV showed increase and decrease in DTAB-β-LA absorption. SDS and DTAB and SDS-rich mixtures of SDS-DTAB form homogeneous solutions with β-LA CD observed that both SDS and DTAB could change the β-LA structure. The effects of the mixtures of SDS-DTAB on β-LA structure depended on the ratio of SDS-DTAB. DTAB and the SDS-rich of SDS-DTAB could significantly affect β-LA structure, while SDS exhibited weaker interaction with β-LA. The fluorescence study indicated a change in the environment of the tryptophan residue of β-lactoglobulin upon binding. Fluorescence quenching, from which binding parameters were evaluated, revealed that the quenching of the β-LA by SDS resulted from the formation of a SDS-β-LA complex. Fluorescence measurements showed that both SDS and DTAB could induce the quenching of fluorescence of β-LA, but DTAB enhanced the β-LA fluorescence when DTAB concentration was above 0.04 mM. The effect of the SDS-rich mixtures of SDS-DTAB on the fluorescence of β-LA became stronger with the increase of the molar fraction of SDS in SDS-DTAB mixtures.